Stability, control and application of time-delay systems - Gao, Qingbin; Karimi, Hamid Reza (Butterworth-Heinemann, an imprint of Elsevier, 2019)
Stability, Control and Application of Time-Delay Systems gives a systematic description of these systems. It includes adequate designs of integrated modeling and control and frequency characterizations. Common themes revolve around creating certain synergies of modeling, analysis, control, computing and applications of time delay systems that achieve robust stability while retaining desired performance quality. The book provides innovative insights into the state-of-the-art of time-delay systems in both theory and practical aspects. It has been edited with an emphasis on presenting constructive theoretical and practical methodological approaches and techniques.
Keywords: Time delay systems.; Feedback control systems.; elektronické knihy; electronic books